Pengetahuan berhubungan dengan Kepatuhan Pasien Hepatitis B dalam Menjalani Terapi Hepatoprotektor - Yusriana Sari; Teti Rahmawati (Universitas Baiturrahim, 2022)
Hepatitis B patients who do not comply with consuming natural medicinal compounds containing hepatoprotective will experience a decrease in health, low antiviral activity, antioxidants for the body and lead to complications of other diseases. The purpose of this study was to determine the relationship between knowledge and patient compliance in undergoing hepatoprotector therapy at the internal medicine polyclinic of Gatot Soebroto Hospital. This study used a cross sectional design. The number of samples in this study were patients with chronic hepatitis B at the Internal Medicine Polyclinic of the RSPAD as many as 98 respondents. The results showed that most of the patients who underwent hepatoprotector therapy were male, aged between 45-59 years, and had a high school education. The patient's knowledge about hepatitis B was classified as good at 65%. Patient compliance in undergoing hepatoprotector therapy was classified as partuh as much as 57%. There is a significant relationship between knowledge of hepatitis B and patient compliance in undergoing hepatoprotector therapy at the internal medicine polyclinic of Gatot Soebroto Army Hospital. The research suggestion is that nurses who have not attended training should be given training immediately so that the procedure for providing therapy for chronic hepatitis B sufferers that has been determined by the hospital can be carried out properly and correctly by allnurses.